Uso de las aplicaciones móviles (Google Translate, Duolingo, y otros) como herramientas para la comunicación del idioma inglés y su aporte al desempeño laboral de las secretarias de la Empresa REYBANPAC de la ciudad de San Juan de la Provincia de Los Ríos - Monserrate Onofre, Betzaida Denny (2020)
The present investigation was carried out in order to determine the use of mobile translation applications as a tool for communication in the English language in the secretaries of the Reybanpac company in the San Juan parish of the Los Ríos province, since the English language is part of daily life when the company is engaged in international trade, in the same way mobile translation applications play a fundamental role in carrying out these commercial agreements. To carry out this case study, survey and interview techniques were used, which were used both for secretaries and administrative staff with the sole purpose of collecting all the necessary information and in such a way to reach a conclusion that allows to achieve the development of the organization, so that having knowledge of the English language is essential today both for personal life and in the professional field. It was evident that the secretaries consider that translation applications are very useful but that most of them do not use them, because they have knowledge of English, in addition to having personnel trained in the language to carry out international business, which he attributes to the success and growth of the company, which is why it can be said that the use of mobile translation applications are useful, however, the best alternative is to have staff trained in the language.